2020
DOI: 10.1161/hypertensionaha.120.14752
|View full text |Cite
|
Sign up to set email alerts
|

STEAP3 (Six-Transmembrane Epithelial Antigen of Prostate 3) Inhibits Pathological Cardiac Hypertrophy

Abstract: Pathological cardiac hypertrophy is one of the major predictors and inducers of heart failure, the end stage of various cardiovascular diseases. However, the molecular mechanisms underlying pathogenesis of pathological cardiac hypertrophy remain largely unknown. Here, we provided the first evidence that STEAP3 (Six-Transmembrane Epithelial Antigen of Prostate 3) is a key negative regulator of this disease. We found that the expression of STEAP3 was reduced in pressure overload-induced hypertrophic hearts and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…To gain insights into the mechanisms by which LAPTM5 regulated the MEK-ERK1/2 signaling pathway, we performed mass spectrometry analysis and identified Rac1, a GTP-binding protein. Numerous studies have confirmed that Rac1 is involved in pressure overload-induced heart failure and the MEK-ERK1/2 signaling pathway (30). In our study, Rac1 was found to be the direct target of LAPTM5 in cardiomyocytes, as LAPTM5 overlaps with the Rac1 protein and interacts with each other.…”
Section: Discussionsupporting
confidence: 73%
“…To gain insights into the mechanisms by which LAPTM5 regulated the MEK-ERK1/2 signaling pathway, we performed mass spectrometry analysis and identified Rac1, a GTP-binding protein. Numerous studies have confirmed that Rac1 is involved in pressure overload-induced heart failure and the MEK-ERK1/2 signaling pathway (30). In our study, Rac1 was found to be the direct target of LAPTM5 in cardiomyocytes, as LAPTM5 overlaps with the Rac1 protein and interacts with each other.…”
Section: Discussionsupporting
confidence: 73%
“…Evidence from Safa et al [ 167 ], Chen et al [ 168 ], Zhou et al [ 169 ], Hu et al [ 170 ], Lou et al [ 171 ], Zhang et al [ 172 ] and Chen et al [ 173 ] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [ 174 ] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…MFAP4 [79], ALOX15 [80], COL1A1 [81], APOA1 [82], PDE5A [83], CX3CR1 [84], THY1 [85], GREM1 [86], FMOD (fibromodulin) [87], NPPA (natriuretic peptide A) [88], LTBP2 [89], LUM (lumican) [90], IL34 [91], NRG1 [92], CXCL14 [93], CXCL10 [94], ACE (angiotensin I converting enzyme) [95], CFTR (ystic fibrosis transmembrane conductance regulator) [96], S100A8 [97], S100A9 [97], HP (haptoglobin) [98] [162], Zhang et al [163] and Chen et al [164] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [165] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…[158], Chen et al [159], Zhou et al [160], Hu et al [161], Lou et al [162], Zhang et al [163] and Chen et al [164] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [165] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%